Stylized Facts on Productivity Growth Evidence from Firm-Level Data in Croatia - Iootty, Mariana (The World Bank, 2014)
Drawing on a representative sample of firms, this paper presents some microeconomic evidence on the productivity growth process in Croatia since the onset of recession (2008-12). Four types of results are highlighted. First, there is a persistent (and increasing) heterogeneity in the performance of Croatian firms along outcome measures. Second, Croatia lags behind regional peers in entrepreneurship measures, which suggests a comparatively lower economic dynamism. Third, the lack of dynamism displayed by the Croatian economy is confirmed when looking at the firm entry and exit process: the analytical results point to reduced firm dynamism compared with Croatia's peers in Europe and Central Asia. Fourth, the contribution of net entry to overall productivity growth in Croatia is surprisingly negative. This is contrary to what would be expected based on the literature and suggests that the process of "destructive creation" in Croatia has not been efficient, as the market might be eliminating firms that are potentially productive. Policies that foster market contestability should be pursued, especially policies aiming at better product market regulation (such as liberalization of entry into the service sector, particularly retail and infrastructure). Measures to help finance entrepreneurship (in promising sectors) should be used to support enhancements in firm productivity. In addition, appropriate bankruptcy rules play a key role by easing the exit process and allowing low-productive units to leave the market and free resources that can be better used by other, more efficient, firms